Transmission or ‘creative fidelity’?: The institutional communicator’s role in the Church today - Gil, Alberto (Church, Communication and Culture, 2020)
The role of the institutional communicator in the Church today has a special relevance derived from the credibility crisis suffered by this institution. A greatly increased awareness to this theme leads to the discovery of profound and essential dimensions of this role, which are discussed in this article. The focus is on the credibility of the communicator, who, on one hand is called to take full responsibility for what he says, but on the other hand speaks in the name of and through a collective subject—the Church or one of its specific constituent parts—that doesn’t always receive much appreciation from its numerous audiences; it is actually often perceived to be “biased” as an institution, it is widely opposed and criticized. An in-depth analysis regarding the role of credibility from a sociological point of view is illustrated by the application of the three roles identified by Erving Goffman—animator, author and principal—to the figure of the institutional communicator, underlining his responsibilities as communication co-leader. A comparison with the concept of translator as a mediator illuminates other characteristics of the communicator, and functions as a basis to comment on some of the virtues (both personal and professional), which he must possess, enhancing both his credibility and efficiency. The application of the concept of creative fidelity (fidélité créatrice) from the French philosopher Gabriel Marcel, together with the interrelation between comprehension and exposition in a comprehensible manner (hermeneutics and creativity), highlights the necessity of reconsidering the importance of communication and of the communicator within the decision-making process.